Catching Ecstasy : Proust and the Tangibilia Beyond Time’s Dimension (Comparatismi, 2023)
The article starts recalling the barthesian notion of Tangibilia, referred to the concrete detail’s device present in Japanese haiku, explicitly related to the Recherche. By retracing earlier Proustian texts it’s shown the persistency of his tension toward this styleme conceived as key of an emotional writing, up to its complete realisation in the Recherche. In this œuvre, thanks to a finally defined conceptual architecture, the detail is invested by the idea of Time; at once, it decisively contributes to structure it and to make it communicable through the instant of Ecstasy. The article concludes with a brief review of interdisciplinary perspective about the detail. It also proposes a possible resolution to Barthes’ problem of passing from Notation to Novel, suggesting that the latter could be considered a producer, more than a container, of the former.